The Faces of Intellectual Disability : Philosophical Reflections - Carlson, Licia, 1970- (Indiana University Press, 2010)
In a challenge to current thinking about cognitive impairment, this book explores what it means to treat people with intellectual disabilities in an ethical manner. Reassessing philosophical views of intellectual disability, Licia Carlson shows how we can affirm the dignity and worth of intellectually disabled people first by ending comparisons to nonhuman animals and then by confronting our fears and discomforts. Carlson presents the complex history of ideas about cognitive disability, the treatment of i.